PENGEMBANGAN DESA WISATA DALAM UPAYA MENINGKATKAN KESEJAHTERAAN MASYARAKAT TELUK SANTONG KABUPATEN SUMBAWA - Elly Karmeli; A Asmini; K Kartiana (Pusat Riset dan Publikasi, 2020)
This study aims to know the efforts to develop a tourist village in improving the welfare of the people of Teluk Santong village, Plampang Sub-District, Sumbawa District. Type of this study was qualitative descriptive study. The data collection technique used was participant observation in the form of direct observations that had done by researcher by involving oneself in various activities in the tourist village. The method of data collection was done through unstructured interviews and documentation. The data analysis technique used in this study was qualitative data analysis which includes data reduction, data presentation, drawing conclusion and verification.The results of data analysis showed that the Teluk Santong tourism village had many natural potentials that can be developed into a tourist village. This was also supported by the willingness, ability, enthusiasm and good communication and can increased economic capacity and creating jobs so as to improve the welfare of the communities in Teluk Santong village.